ANALISIS STRATEGI BISNIS PT. CENTREPARK CITRA CORPORA DI TERAS KOTA MALL TANGERANG SELATAN - Asmadi, Iwan; Wilhamdoni, Wilhamdoni (Yayasan Akrab Pekanbaru, 2019)
This research uses Qualitative Descriptive method through a combination of observation, interview, and questionnaire techniques for all company employees. From the analysis concluded the best policy or decision that will be taken by the company in order to maximize the factors of strength and opportunity factors and overcome threats that are likely to occur and find formulations in overcoming company weaknesses. In the IFE matrix is 2.94 and the EFE matrix is 2.88. According to scale 4, the internal and external positions are actually not strong because the value < 3 is a strong value. However, this weak position tends to be strong considering the distance is not too far to reach value 3. In the IFE matrix the company is not in a safe and unstable position so it needs to minimize weaknesses and threats. In the EFE matrix, companies must also maximize the strengths and opportunities that exist so that the company's position is in a better position.In the CPM matrix that analyzes the competition profile where the position of the company is slightly superior to that of its competitors, PT. Centrepark Citra Corpora of 3.52, PT. Secure Parking Indonesia is value 3.30, VIP Parking is 2.86. This requires companies to try to maximize their ability to win the competition because of the tendency to be able to overtake and beat each other wide open which is reflected in the very low distance between competitors.